The Influence Of Current Ratio, Net Profit, Total Debt And Own Capital On Stock Prices In The Cement Industry On The Indonesian Stock Exchange Period 2011-2015 - Coelho, Agostinho; Artati, Susi (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
This study aims to determine how much influence the share price at the Indonesian Stock Exchange (Case Study at PT. Holcim Indonesia Tbk, PT. Indocement Tbk and PT. Semen Indonesia (Persero) Tbk) and whether there is significant influence Current Ratio, Net Income Total Debt and Equity on stock price on the Indonesia Stock Exchange Period 20112016. The analytical method used is multiple linear regression analysis. Hypothesis testing is done by statistical test simultaneous test (F test) and partial test (t test). Samples are companies listed on the Indonesia Stock Exchange. Analysis of the regression results do after experiencing symptoms multikolinearity assumptions, autocorrelation and heteroscedasticity. From the results paerhitungan using SPSS program by comparing with the significant level ? = 0.05 (5%). It can be seen that amounted to 37,612 by comparing ? = 0.05 with 4 degrees of freedom numerator and denominator degrees of freedom 10, obtained at 3,48. greater than (37,612 > 3,48), then Ho is rejected and Ha accepted. Thus it is said that the variable Current Ratio, Net Income, Total Debt and Equity together (simultaneously) has significant influence on stock prices. Partially Current Ratio and Total Debt has a significant influence on stock prices. Meanwhile, Net Income and Capital itself does not have a significant effect on stock price. Conlution is in this research should encourage more enterprise level Current Ratio and Total Debt, because the Current Ratio and Total Debt has a great influence (0,609 and 0,600) and a significant increase in stock price on Cement Industry listed on the Indonesia Stock Exchange. For investors who choose to invest in Cement Industry listed on the Indonesian Stock Exchange may consider the Current Ratio and Total Debt has a significant effect simultaneously.